Le rôle de l’agent et du courtier en assurance - Clermont, André J. (Assurances)

(untitled) (HEC Montréal, 1992)
Courts are placing a greater burden of responsibility on insurance agents and brokers, with respect to potential liability. First, the author discusses the difference between the terms "agent" and "broker" from a legal standpoint, then he analyzes current issues such as the true role of the agent as an intermediary, the "two hat syndrome" of insurance agents and brokers and, lastly, their emerging new duties.